The community care model (CCM) for multi-drug resistant of tuberculosis (MDR-TB) patient with social engagement: A case study province located at lower northeastern part, Thailand - Srithongtham, Orathai; Ponboopha, Aomtip; Naknikorn, Thananphat; Leungratanamart, Norapat; Chualee, Satian; Inyaphong, Jiraphun; Wongkrai, Ketsuma; Buaphan, Pattaraporn (Open Science Journal, 2021)
This research was aimed to develop the community care model for Multi-Drug Resistant of Tuberculosis (MDR-TB) patient and to evaluate the community care for MDR-TB patient model. Four steps of method were (1) identify the problem, (2) performance enhancement, (3) model development, and (4) implementation. The 36 sub-districts from 12 districts where found MDR-TB patient was the study areas. Target groups were consisted of MDR-TB patient, TB Clinic people from district and sub-district hospital, care giver who care on drug observe therapy (Dot) to MDR-TB patient, and community leader. Research tools were questionnaires, interview guide, and venue of participation of the stake holders. The data analysis was used descriptive statistics for quantitative data and content analysis for qualitative data. The model of Multi-drug Resistance Tuberculosis (MDR-TB) Patient Care, “Srisaket Model” was 4 phrases; (1) Early access, “Prepare the readiness of care team”, 2-7 day before registered to treatment. Care team at sub-district level was provided MDR-TB case report and communicated to care team, patient assessment, stop taking any drug in case of TB old case, and prepare the readiness for MDR-TB treatment. (2) In-hospital care, “Start treatment and care as MDR-TB patient”, 14-28 day in the hospital. The essential activities were case management; prepare team and community to care of the patient, disease investigation and screening TB contact case. (3) Intensive care, “Dot by heart”, 3-6 months, the core activities was Dot, drug injection, quality drug assurance and averse drug management (ADM), and prepare area zone for care of MDR-TB patient followed the Infectious control guideline for TB/MDR-TB. And (4) Continuum care, “Cooperation to cope the disease”, Dot care continuously, surveillance to ADM, discharge plan and continuously 5 years plan for TB contact cases surveillance by Chest X-ray and for relapse of TB/MDR-TB patient.